2014
DOI: 10.1007/s12035-014-8927-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Expression of Parkinson’s Disease-Related Mitochondrial Abnormalities in PINK1 Knockout Rats

Abstract: PTEN-induced kinase 1 (PINK1) mutations are responsible for an autosomal recessive, familial form of Parkinson’s disease. PINK1 protein is a Ser/Thr kinase localized to the mitochondrial membrane and is involved in many processes including mitochondrial trafficking, mitophagy, and proteasomal function. Using a new PINK1 KO rat model we found altered brain metabolomic markers using magnetic resonance spectroscopy, identified changes in mitochondrial pathways with quantitative proteomics using sequential window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 73 publications
4
91
3
Order By: Relevance
“…All experimental animals were males, because prior studies reporting neurodegeneration in PINK1 KO rats were performed exclusively in males (Dave et al, 2014; Grant et al, 2015) or were not reported (Villeneuve et al, 2016). Colonies ofWT and PINK1 KO Long-Evans Hooded rats were established from founders obtained from SAGE Labs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experimental animals were males, because prior studies reporting neurodegeneration in PINK1 KO rats were performed exclusively in males (Dave et al, 2014; Grant et al, 2015) or were not reported (Villeneuve et al, 2016). Colonies ofWT and PINK1 KO Long-Evans Hooded rats were established from founders obtained from SAGE Labs.…”
Section: Methodsmentioning
confidence: 99%
“…However, while PINK1 knockout (KO) or mutant flies have systemic phenotypes, including severe muscle degeneration associated with severe mitochondrial dysfunction (Clark et al, 2006; Park et al, 2006), PINK1 KO mice show only altered dopamine homeostasis without neurodegeneration (Kitada et al, 2007). In contrast, loss of PINK1 in rats causes many behavioral phenotypes between 2 and 8 months of age, prominent changes in catecholamine levels by 8 months of age and, most importantly, loss of ~50% DA neurons in the SN by 8–9 months of age (Dave et al, 2014; Villeneuve et al, 2016). However, this degeneration was not observed in a study that used a non-stereological method of quantitation (Grant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(1) The majority of studies utilise proliferating cell lines and although such systems are unrivalled for the tractable [31,32]. In contrast, Parkin KO rats do not exhibit significant PD-related pathology due to probable redundancy of E3 ubiquitin ligases, for example MUL1 [26].…”
Section: Pink1 Phospho-ubiquitin (P-ub) Parkin and The Regulation Omentioning
confidence: 99%
“…Similar to Parkin knockout mice (Goldberg et al 2003), PINK1 knockout mice do not develop nigral dopamine neuron loss but exhibit mitochondrial respiration defects in the striatum but not in the cortex at 3–4 months (Kitada et al 2007; Zhou et al 2007; Gispert et al 2009; Akundi et al 2011). Multiple groups have reported significant nigral cell loss in 8–9 month old PINK1 knockout rats using rigorous stereology (Dave et al 2014; Villeneuve et al 2014). …”
Section: Domain Structures and Functions Of Parkin And Pink1mentioning
confidence: 99%